(untitled) (Annals of Medical Research, 2021)
Aim: Breast cancer-related lymphedema (BCRL) is a disabling complication that can develop following breast cancer surgery months or even years after treatment ends. The effective management of BCRL requires adhering to simple risk-reduction strategies. The study aim was to assess the awareness and knowledge of lymphedema risk-management behaviors among breast cancer survivors and identify factors that affect it. Material and Methods: This study was conducted on 250 survivors of breast cancer. Demographic information, treatment details, time since surgery, duration and stage of lymphedema were recorded. Lymphedema education, knowledge about risk-minimization recommendations, and information sources were questioned using a survey. A multiple linear regression was used to identify predictors of lymphedema awareness.Results: Just over half (53.6%) of the patients had adequate lymphedema awareness (score≥8). BCRL was detected in 121 (48.4%) patients. Awareness scores varied by age, education level, body mass index, receiving chemotherapy and radiotherapy, and a previous BCRL treatment (all p0.05). Citing physiatrists as an information source reflected higher levels of awareness. Educational level and axillary lymph node dissection were positive predictors; time since surgery was the only negative predictor of lymphedema awareness. Conclusion: This study highlights the lack of lymphedema awareness among survivors of breast cancer. Accurate, timely, individualized training programs can improve knowledge and compliance of lymphedema risk management behaviors.